2022
DOI: 10.37291/2717638x.202233193
|View full text |Cite
|
Sign up to set email alerts
|

Are you listening to me? Understanding children's rights through Hungarian pedagogic practice

Abstract: Hungarian pedagogues agree that children should be listened to, have their rights recognised, and their voices heard.  The UNCRC recommends that children’s rights should be part of early childhood education, but this is not typical in Hungarian kindergartens and there is little pedagogical material to support the education of children about their rights.  This paper focuses on 5 kindergartens each typically accommodating over 150 children between the ages of 3-6 years old across Hungary. Six pedagogues worked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…We found that participants told similar stories in which they referred to concerns about how to continue to teach children traditions. We also found similarities between Habinyák (2022), Rădulescu (2006) and Canning et al (2022) research, and our research outcomes. Resistance to change was evident and it was assigned to cultural and historical weight of expectation that shapes values and beliefs the kindergarten pedagogues.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We found that participants told similar stories in which they referred to concerns about how to continue to teach children traditions. We also found similarities between Habinyák (2022), Rădulescu (2006) and Canning et al (2022) research, and our research outcomes. Resistance to change was evident and it was assigned to cultural and historical weight of expectation that shapes values and beliefs the kindergarten pedagogues.…”
Section: Discussionsupporting
confidence: 71%
“…After the fall of the communist regime Habinyák (2022) further argued that teachers found it challenging to respond to the curriculum change, and reported that early learning still follows strict educational rules. In Hungary, Canning et al (2022) observed a similar pattern. They stipulated that incorporating child-led ECE practices could be challenging, as their voices intertwines with the routine of daily practice and they act as an influential force that present potential barriers to adopting change.…”
Section: Responses To Changesupporting
confidence: 55%
See 1 more Smart Citation
“…This policy ensured the use of the Hungarian language in educational institutions, especially when, in 1977, a new education law was passed that encouraged the use of the mother tongue (Tóth 1994;Wright et al 2000). The state attributed great significance to the education of citizens following a strictly normative and outcome-driven framework and requiring unconditional obedience to ideological expectations (Canning et al 2022;Bogic 2018). The identity was also shaped by the state's patriarchal and masculine ideology of family patterns (Milićević 2006).…”
Section: Context Of the Studymentioning
confidence: 99%
“…Smith (2015) underlines the principle of respect for the child's views and feelings outlined by the United Nations Committee on the Rights of the Child (UNCRC) and argues that this principle should be enacted in all Early Childhood Education (ECE) settings. Canning et al's (2022) study of Hungarian kindergartens highlights the importance of including children's voices through play-based creative activities that focus on eliciting children's thoughts and feelings and providing insight into their lives.…”
Section: Introductionmentioning
confidence: 99%